1992
DOI: 10.1177/030089169207800205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immune Response in the Prognosis of Carcinoma of the Uterine Cervix: Can in Vitro Analysis Provide a better Framework for more Effective Management?

Abstract: Cancer of the uterine cervix is the single largest female malignancy in India and also remains a major problem facing oncologists in other parts of the world. While advances in radiation therapy and surgical techniques have made the treatment of cervical carcinoma impressive, limitations to successful management still remain. In fact, the 5-year survival rate, stage for stage, has not improved in the United States or world wide in the past 40 years. With an estimated half a million women developing this diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Preliminary studies reported by us and others in oral cancer reveal gross immunological alterations in terms of increased circulating immune complexes , imbalance of lymphocyte populations (Balaram et al 1983;Pillai et al 1987), lymphocyte functions (Cheriyan et al 2009;Balaram et al 1984), serum blocking effects (Balaram et al 1984;Pillai et al 1988) and kinetics of target cell lysis (Pillai et al 1990a). We have also shown in cancer of the uterine cervix that irrespective of the stage of the disease, the patients could be classified into those with adequate immune responses and depressed immune responses, both groups falling in the same stage of the disease.…”
Section: Introductionmentioning
confidence: 97%
“…Preliminary studies reported by us and others in oral cancer reveal gross immunological alterations in terms of increased circulating immune complexes , imbalance of lymphocyte populations (Balaram et al 1983;Pillai et al 1987), lymphocyte functions (Cheriyan et al 2009;Balaram et al 1984), serum blocking effects (Balaram et al 1984;Pillai et al 1988) and kinetics of target cell lysis (Pillai et al 1990a). We have also shown in cancer of the uterine cervix that irrespective of the stage of the disease, the patients could be classified into those with adequate immune responses and depressed immune responses, both groups falling in the same stage of the disease.…”
Section: Introductionmentioning
confidence: 97%